Women's education in dagestan during the first decades of the soviet power in the regional historiography of 1920s - 1930s - Ghani Shikhvalievich Kaimarazov; Leyla Ghanievna Kaymarazova (Вестник Майкопского государственного технологического университета, 2023)
The article considers the relevant problem of ensuring access of the female population to all forms of education at the initial stage of the Soviet modernization in the multinational region of the country, where significant influence norms of Islam and local traditions remained during the considered period under review. The authors use the principle of historicism, comparative historical, chronological, statistical methods and a systematic approach to show that regional historiographic developments have preserved unique evidence of the fact that in the 1920s - 1930s mountain women of the multinational mountainous region eliminated their illiteracy, and the availability of basic, secondary and higher vocational education allowed them to take a worthy place in various sectors of the national economy and culture. The authors of the described works were public and state figures, practitioners, correspondents of periodicals, demonstrating their commitment to the ideas of socialism, socialist construction; they contributed significantly to the regional Historiography of women's history in the 1920s - 1930s, laying the foundations for research for future generations of historians.